Cone Beam Computed Tomography Analysis Of Remaining Dentin Thickness On Instrumenting Extracted Premolars With Different Rotary Niti File Systems- An In-Vitro Study - Swathi.S; S.Delphine Priscilla Antony; Pradeep Solete; Adimulapu Hima Sandeep (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Aim: The current study aimed at assessing the remaining dentin thickness on instrumenting extracted premolars with various file systems. Materials And Methods: 30 extracted single rooted mandibular premolars were collected. Access cavity preparation was done and working length determined. Following the pre-cone-beam computed tomography (CBCT) scan, the corresponding file groups were prepared biomechanically. Group I – Protaper Gold, Group II –ProFit S3, and Group III – Neo Endo. Post-CBCT scan was taken and the pre- and post-CBCT scans were compared for remaining dentin thickness. Following the pre-cone-beam computed tomography (CBCT) scan, the corresponding file groups were prepared biomechanically and analyzed with ANOVA (P = 0.001). Results: Among three different rotary endodontic files, S3 showed minimum reduction in dentin thickness followed by Neo Endo and Protaper Gold and there was a statistical significant difference between intergroups (p=0.01). Conclusion: ProFit S3 shown to be effective in preserving the remaining dentin thickness as compared to other groups.